Effect of self-modeling and self-controlled feedback on the performance of professional swimmers and waterpolo players - Mirmoezzi, M.; Sayyah, M.; Taheri, M.; Irandoust, K.; Sangari, M.; Mirakhori, F.; Seghatoleslami, A.; Hill, L.; Weiss, K.; Knechtl, B.; Ghram, A. (Sports Medicine and Health Science, 2023)
Self-modeling (SM) and self-control (SC) feedback can be presented as two solutions for learning improvement. Therefore, the aim of the present study was to investigate the effects of SM and SC feedback on 100-m freestyle performance of professional swimmers and waterpolo players. 25 elite male swimmers and waterpolo players, were randomly assigned to four groups: swimmer group with SM, swimmer group with SM and SC feedback, waterpolo players group with SM, and waterpolo players group with SM and SC feedback. 100-m freestyle times and performance were recorded. SM and SC feedback for the participants were utilized at the acquisition stage. The device used included a Lenovo B570 laptop and an Exilim ZR200 canon camcorder. SM and SC feedback presented to the swimmers and waterpolo players led to improved speed and results, and the effect of presenting SM with SC feedback to swimmers had better results. In conclusion, the present study indicates that SC modeling of watching video is a suitable method for professional swimmers. Water polo trainers can also use SM and SC feedback to enhance their players' swimming technique.